Learning to share knowledge for global agricultural progress - Staiger Rivas, Simone; Galiè, Alessandra; Hack, Bernhard; Jorge, M.A.B.; Meadu, Vanessa; Tateossian, F.; Salokhe, G.; White, N. (Inderscience Publishers, 2010)
Web 2.0 tools combined with face-to-face methods offer new opportunities for better knowledge sharing across disciplines, languages and borders. This article comprises an overview and case studies – the personal accounts of six participants and one facilitator of a 2008 Workshop on Knowledge Sharing, sponsored by the Consultative Group on International Agricultural Research. It lays out the rationale for, and lessons learned from, those efforts, as well as from a second workshop hosted by the Food and Agriculture Organization of the United Nations. It explains why, in today's culture of self-directed learning, group experiences remain essential. The authors describe their learning trajectories and application of knowledge sharing tools and methods in their work.